2016
DOI: 10.1158/0008-5472.can-15-2936
|View full text |Cite
|
Sign up to set email alerts
|

miR-1298 Inhibits Mutant KRAS-Driven Tumor Growth by Repressing FAK and LAMB3

Abstract: Global microRNA functional screens can offer a strategy to identify synthetic lethal interactions in cancer cells that might be exploited therapeutically. In this study, we applied this strategy to identify novel gene interactions in KRAS mutant cancer cells. In this manner, we discovered miR-1298, a novel miRNA that inhibited the growth of KRAS-driven cells both in vitro and in vivo. Using miR-TRAP affinity purification technology, we identified the tyrosine kinase FAK and the laminin subunit LAMB3 as functio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 39 publications
0
41
0
Order By: Relevance
“…These cell lines have previously been used by our lab to conduct a high-throughput screen of oncogenic KRAS synthetic lethal microRNAs (13). We transduced HCT116 WT and HCT116 MUT cells with the human GeCKO v2 library, which contains 65,383 sgRNA constructs targeting 19,050 human coding genes (3 sgRNAs per gene) and 1864 microRNAs (4 sgRNAs per gene) (8).…”
Section: Resultsmentioning
confidence: 99%
“…These cell lines have previously been used by our lab to conduct a high-throughput screen of oncogenic KRAS synthetic lethal microRNAs (13). We transduced HCT116 WT and HCT116 MUT cells with the human GeCKO v2 library, which contains 65,383 sgRNA constructs targeting 19,050 human coding genes (3 sgRNAs per gene) and 1864 microRNAs (4 sgRNAs per gene) (8).…”
Section: Resultsmentioning
confidence: 99%
“…Although this study provided a novel insight into the functional role of miR-1298 in NSCLC, the underlying mechanisms remain unclear. A study by Zhou et al indicated that miR-1298 could inhibit the mutation of KRAS, which serves as an oncogene in human malignancies, leading to the suppression in tumor growth [15]. In addition, Li et al demonstrated that miR-1298-5p exerted inhibiting effects on bladder cancer cell proliferation and invasion by downregulating connexin 43 [32].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Xu et al analyzed the deregulated miR-NAs in NSCLC in silico, and microRNA-1298 (miR-1298) was found to be decreased in tumor cases compared with the normal controls [14]. Another study by Zhou et al indicates that miR-1298 is closely related with the KRAS mutation, which is determined as a key event during lung cancer progression [15]. However, the expression patterns of miR-1298 in NSCLC patients and its biological function are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…miR-1298 was identified in a global miRNA functional screen as selectively lethal to cells expressing mutated KRAS, which is an oncogene mutated in 20% of human cancers, mainly NSCLC and colorectal cancers. miR-1298 acts a tumor suppressor in KRAS-driven NSCLC and colorectal cancer cells by directly targeting the mRNA of both FAK and the Laminin subunit beta 3 (LAMB3), lowering their protein expression levels [153]. Interestingly, only expression of LAMB3, but not FAK, was upregulated by KRAS; yet silencing of either FAK or LAMB3 recapitulated miR-1298-induced cell-death in KRAS-dependent cancer cells.…”
Section: Non-coding Rnamentioning
confidence: 99%